Effects of amniotic membrane extract on primary human corneal epithelial and limbal cells. (15th January 2015) - Dudok, David V; Nagdee, Imraan; Cheung, Kevin; Liu, Hong; Vedovelli, Luca; Ghinelli, Emiliano; Kenyon, Kenneth; Parapuram, Sunil; Hutnik, Cindy M
Abstract Background To assess the effects of amniotic membrane extract (AMX) on cellular activity of primary human corneal epithelial (HCE) cells under mechanical and oxidative stress, and on human limbal cells under oxidative stress. Methods Corneal mechanical stress was simulated with a linear scratch in confluent HCE cell plates, then incubated with 0.1% AMX for 48 and 72 h. Subjecting HCE cultures to 0.5 mmol/L tertiary‐butylhydroperoxide for 1 h simulated an oxidative stress. 0.1% AMX‐treated cultures were compared with controls at 24 and 48 h using cellular viability assay, along with 12‐h AMX pretreatment and human limbal cell comparisons. Results Mechanical stress on HCE cultures revealed a statistically significant distance ratio at 48 and 72 h in favour of 0.1% AMX‐treated cultures (P = 0.021 and 0.035, respectively). Oxidative stress did not reveal any significant difference in cellular viability of AMX‐treated versus control cultures. Twelve hour AMX pre‐treatment prior to oxidative stress revealed a significant difference after 24 h from oxidative injury (73.3% AMX vs. 66.0% control, P = 0.035), but not after 48 h. Human limbal cells demonstrated significantly improved oxidative viability compared with HCE cells, with (91.0% vs. 82.0% control, P = 0.017) and without 0.1% AMX pre‐treatment (91.2% vs. 83.7% control, P = 0.019). Conclusions HCE cells treated with AMX healed faster after mechanical insult, suggesting a potential benefit in acute corneal injuries. Under oxidative stress, human limbal cells, a more proliferative cell type, showed superior viability compared with HCE cells.